PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS PEGAWAI PADA BANK SAMPAH SIMPATIK PROJECK DI NAGORI SIDAMANIK - Purba, Johanes; Purba, Fariaman; Lubis, Febrina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The formulation in this study is how the influence of workload and work stress on employee productivity at the Simpatik Waste Bank Project in Nagori Sait Buttu, Sidamanik District. The purpose of the study was to examine the effect of workload and work stress on employee productivity at the Simpatik Waste Bank Project. The sample of this research is 20 employees. The analysis technique of this research uses multiple linear regression test Y=3.224+0.454 X1+0.390X2 where the constant y is (3.224) and the workload is (0.454) and the work stress is (0.390) which is significant. t test analysis (3.201>2.1010) was significant. Showing significant results This is indicated by the magnitude of the value. F analysis of 16,813 with a significant level of 0.000 (less than 0.05). Meanwhile, from the results of the calculation of the coefficient of determination (R2), it can be seen or concluded that the independent variables in this study were able to explain 62.5% of the dependent variable (Employee Productivity) of the Sympathetic Waste Bank Project. While the remaining 37.5% is influenced by data factors that are not examined. it can be concluded that Ha is accepted or workload and work stress have a significant effect on employee productivity.